Monetary Theory and Policy - Walsh, Carl E. (The MIT Press, 2012)
Monetary Theory and Policy presents an advanced treatment of critical topics in monetary economics and the models economists use to investigate the interactions between real and monetary factors. It provides extensive coverage of general equilibrium models of money, models of the short-run real effects of monetary policy, and game-theoretic approaches to monetary policy. Among the topics covered are money-in-the-utility-function models, cash-in-advance models, money and public finance, the credit channel of money, models of time consistency, monetary policy operating procedures, and interest rates and monetary policy.